Chemical control of the two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Tetranychus urticae; control; insecticides; fungicides; leaf disc method; vial residue method Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 59-62